Hybrid Off-pump Second-Stage Aortic Arch Repair after Type A Dissection - Lescan, Mario; Andic, Mateja; Krüger, Tobias; Ivosevic, Vedran; Schlensak, Christian (The Thoracic and Cardiovascular Surgeon, 2019)
Background Ascending aorta or hemi-arch repair are common in the acute phase of type A dissection. Postdissection aneurysms can develop with antegrade perfusion of the false lumen in the dissected aortic arch and require reoperation.Methods From 2012 to 2018, we reoperated nine patients with postdissection aneurysms using a hybrid technique without cardiopulmonary bypass. The patients had a EuroSCORE II of 13% and a logistic EuroSCORE I of 45% and were not candidates for frozen elephant trunk surgery. The median interval since the acute ascending repair was 184 (92; 528) days. All patients were treated by median resternotomy, ascending to carotid bypass on a partially clamped ascending graft, and transfemoral endovascular repair with a Relay NBS (nonbare stent) or conformable Gore C-TAG stent graft.Results Technical success was achieved in all cases. Mean follow-up was 405 (220; 672) days. There was no disabling stroke, endoleak, paraplegia, in-hospital, or late mortality. In all patients, the false lumen was completely thrombosed at the aortic arch level with a median aneurysm shrinkage of 13 mm in the distal arch. There was no bird beak or stent graft migration. Distal stent-induced new entry was observed in one case. Reinterventions were not necessary due to diameter stability.Conclusion Complete debranching with transfemoral thoracic endovascular aneurysm repair showed encouraging results in patients with relevant comorbidities. The used stent grafts performed well in the mid-term follow-up period with no endoleaks or migration.
Keywords: aorta; dissection; stent graft; TEVAR; aneurysm